Tanggung Jawab Dokter/Rumah Sakit Akibat Malpraktik Medis SebagaiUpaya Perlindungan Hukum Bagi Pasien - Aris Priyadi (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2024)
The relationship between a doctor and a patient is basically a civil law relationship, where the patient comes to thedoctor to cure his illness and the doctor promises to try to treat or cure the illness. Civil relations are legal relationscarried out by parties who are in equal positions. The relationship between the doctor and the patient gives rise torights and obligations or in other words the agreement/agreement between the doctor and the patient gives rise toan obligation, in this case a business contract (inspanning verbintennis) because it is based on an obligation to dobusiness. Doctors are obliged to provide care with care and attention in accordance with professional standards. Soif the patient/family finds out that the doctor has not fulfilled his obligations as stated in the agreement, he can file alawsuit for breach of contract before the court and ask for the agreement to be fulfilled and can demandcompensation. Likewise, if a doctor in his service to a patient commits an act that violates the law, then inaccordance with the provisions of Article 1365 of the Civil Code which regulates unlawful acts, the plaintiff (victim,patient) can demand compensation, both material and immaterial. The principle of the reverse burden of proof canbe applied in medical cases, so the rights of the patient (plaintiff) will be protected, meaning that the plaintiff(patient), even though it is difficult or impossible to prove the fault of the defendant (doctor, hospital) and will stillobtain his rights, namely in the form of compensation both material and immaterial.Keywords: Doctor's liability, malpractice, medica